Blended Learning (WA Group dan Kunjungan Siswa) Solusi Pembelajaran Jarak Jauh di SMP Negeri 3 Kalibagor - Daryanto (UM Purwokerto Press, 2021)
During the Covid-19 pandemic, learning at SMP N 3 Kalibagor must continue, but various obstacles arise in distance learning. Limitations of internet quota, feeling lazy and bored with studying alone at home and limited internet coverage in the area around the school are obstacles. The teacher must be able to find the right distance learning solution so that it can serve the learning of all students with all their limitations and problems. Observation and interviews are the right methods for obtaining data from students and teachers. Blended learning between online and offline PJJ is an alternative that can be implemented to overcome PJJ during the Covid pandemic 19 Learning communication with class group WA is used to provide material and assignment information learning. Offline learning activities with visits to students' homes or study groups need to be done to serve students who have problems and limitations. Activities visiting students can provide a spirit of motivation and character education for students. Blended learning by combining WA class groups and student home visits and study groups is an appropriate alternative in distance learning.